ANALISIS PEMAHAMAN GURU DALAM IMPLEMENTASI KURIKULUM MERDEKA DI SDN 105 PEKANBARU - Fifi Alayda Zahra; Urfa Ernalia, Zarra Hanura Il, M.Jaya Adi Putra, Mauliatun Nisa (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2024)
This research explores teachers' experiences and views in implementing Merdeka Curriculum at SDN 105 Pekanbaru. Through semi-structured interviews with two teachers, this study found that Merdeka Curriculum offers a more flexible and student-centered approach, allowing the adjustment of teaching materials and learning methods according to local needs and student abilities. Although there are challenges in implementation, such as difficulties in creating learning media and the need for a variety of more creative methods, collaboration between teachers, the use of technology, and student motivation are key to success. This research concludes that Merdeka Curriculum has the potential to improve the quality of education at SDN 105 Pekanbaru, with opportunities for innovation, collaboration and great improvements in the quality of education